The Survival of Total Knee Arthroplasty: Current Data from Registries on Tribology: Review Article. Issue 1 (February 2017) - Civinini, Roberto; Carulli, Christian; Matassi, Fabrizio; Lepri, Andrea Cozzi; Sirleo, Luigi; Innocenti, Massimo
Background: Polyethylene (PE) wear is a major contributor to implant loosening following total knee arthroplasty (TKA), and advanced bearings in TKA are being investigated with hopes of reducing or eliminate wear-related loosening. Currently, information on knee tribology is available from national joint registries and may be the best tools to evaluate the efficacy and safety of design innovations in joint arthroplasty. Questions/Purposes: We performed a review of national joint registries trying to answer the following questions: "Which is the main factor directly related to revisions rate in TKA?" and "Are there new bearing options better than conventional ones?" Methods: A review was performed of all published annual reports of National Joint Registers, as well as of the literature. The search was carried out using and comparing the National Joint Registers. Results: Current data from registries for total knee arthroplasty indicates that age is the major factor affecting the outcome of primary total knee replacement. The 10-year cumulative revision rate for non-cross-linked PE was 5.8% and for XLPE it was 3.5%. The effect of cross-linked polyethylene was more evident in the younger patients. The survival of the oxidized zirconium (OxZr) femoral component appears better when compared to a similar age group of patients with conventional group of prostheses. Our review suggests that the revision rates are half for the OxZr components compared to conventional CoCr femoral components. Conclusions: Age is the most relevant single factor related to revision rate. Cross-linked PE has a statistical lower revision rate at 10 years compared to conventional PE and, in the OxZr group, the revision rate is 2 times lower than Co-Cr in the same group of age.